0-3 Yaş Grubu Çocukların Uyku Alışkanlıklarının Belirlenmesi / Determining the Sleeping Habits of Toddlers Aged 0-3 - Gözün Kahraman, Özlem; Ceylan, Şehnaz (Journal of History Culture and Art Research, 2018)
Abstract This study aims to determine the sleeping habits of toddlers aged 0-3. The characteristics of the places where toddlers sleep, the way they go into sleep, and if they have sleeping problems or not are examined with regard to different varieties through descriptive scanning model. The participants are 325 mothers who have toddlers aged 0-3. In order to understand toddlers’ sleeping situations, a questionnaire developed by researchers and personal information form consisting of toddlers’ socio-demographic and relevant information (age, gender, the educational background of parents) were used. Crosstab was used to determine the participants’ descriptive characteristics. When the characteristics of the places where toddlers sleep were examined according to ages, it was found out that most of the toddlers slept in the same room with their parents and this rate decreased as the age increased. They mostly sleep through ways in which parental engagement was required more such as craddling, sucking mom or the pacifier, or being with parents. The sleeping problems were more likely experienced in toddlers between 7-24 months, boys, and those whose parents are university graduates. Also, the rate of experiencing sleeping problems was found higher in parents who give tablets to their toddlers and who let their toddlers watch TV for two or more hours. It has been found that children who are told to be hard tempered have a higher sleeping problem. Considering these findings, the role of parents’ attitudes and preventing interventions was found to be important in establishing the sleeping habits of toddlers. Öz Bu araştırmada 0-3 yaş grubu çocukların uyku alışkanlıklarının belirlenmesi amaçlanmıştır. Çalışmada çocukların uyudukları yere ait özellikler, uykuya geçiş şekilleri ve uyku probleminin olup olmadığı çeşitli değişkenler açısından incelenmiştir. Araştırmada betimsel tarama modeli kullanılmıştır. Araştırmaya 0-3 yaş grubu çocuğa sahip 325 anne katılmıştır. Araştırmada çocukların uyku durumlarını belirlemek amacıyla araştırmacılar tarafından oluşturulmuş anket ve çocuğun sosyo-demografik özellikleri ile ilgili bilgilerin bulunduğu (yaş, cinsiyet, anne- babanın öğrenim durumu) kişisel bilgi formu kullanılmıştır. Çalışma grubunun betimsel niteliklerinin belirlenmesinde çapraz tablolar kullanılmıştır. Çocukların uyudukları yere ait özellikler yaşlarına göre incelendiğinde tüm gruplarda çocukların büyük çoğunluğunun anne babasıyla aynı odada uyuduğu ve bu oranın yaş ilerledikçe azaldığı görülmüştür. Küçük çocukların çoğunlukla sallanarak, anneyi emerek ya da emzikle, ebeveynlerin yanında bulunmasıyla uykuya dalma gibi daha çok ebeveyn katılımını gerektiren yöntemlerle uykuya geçtikleri görülmüştür. 7-24 ay arası çocuklarda, erkek çocuklarında ve üniversite mezunu anne ve babaların çocuklarında uyku problemi görülme oranının daha yüksek olduğu belirlenmiştir. Ayrıca çocuklarına tablet-telefon veren, iki saat ve üzeri televizyon izletilen annelerin çocuklarında uyku problemi görülme oranın da fazla olduğu görülmüştür. Anneler tarafından zor mizaçlı olduğu ifade edilen çocukların daha yüksek oranda uyku problemi gösterdiği saptanmıştır. Bu bulgular neticesinde küçük çocukların uyku alışkanlıklarının oluşmasında ebeveynlerin uygulamalarının belirleyici olduğu ve uyku konusunda önleyici müdahalelerin önemi vurgulanmıştır.